2022
DOI: 10.31557/apjcp.2022.23.7.2449
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Pretherapeutic Diffusion-Weighted MR Imaging Derived Apparent Diffusion Coefficient in Predicting Clinical Outcomes in Immunocompetent Patients with Primary CNS Lymphoma: A Systematic Review and Meta-Analysis

Abstract: Primary Central Nervous System Lymphoma (PCNSL) is an extra-nodal non-Hodgkin lymphoma (NHL) confined to the brain, spinal cord, leptomeninges, or eyes, in the absence of systemic lymphoma at the time of diagnosis. According to studies, PCNSL affects 4-7% of all brain tumors, 5% of all extra-nodal lymphomas, and less than 1% of all non-Hodgkin's lymphoma (Lauw et al., 2020). Around 90% of PCNSL cases exhibit histopathological features consistent with diffuse large B-cell lymphoma (DLBCL). The remainder is comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Although PCNSL is an aggressive tumor, tumor cells infiltrate and destroy the blood vessel wall, and the mechanism of vascular edema is formed by perivascular exudation, which result in a significant decrease in the osmotic pressure of peritumoral blood vessels, and the diffusion of water molecules is not limited, leading to a significant increase in ADC value [ 33 ]. The study has shown that the minimum ADC value of tumor can more accurately reflect the internal biological characteristics and malignancy of tumor tissue, which has become a "hot spot" in tumor differential diagnosis research in recent years [ 34 ]. The augmentation index level of the strong positive VM group was higher, and the in-depth analysis may be due to the fact that the contrast medium could enter with the plasma and diffuse through the tumor space, so that the contrast medium in the gap increased, thereby enhancing the tumor strengthening.…”
Section: Discussionmentioning
confidence: 99%
“…Although PCNSL is an aggressive tumor, tumor cells infiltrate and destroy the blood vessel wall, and the mechanism of vascular edema is formed by perivascular exudation, which result in a significant decrease in the osmotic pressure of peritumoral blood vessels, and the diffusion of water molecules is not limited, leading to a significant increase in ADC value [ 33 ]. The study has shown that the minimum ADC value of tumor can more accurately reflect the internal biological characteristics and malignancy of tumor tissue, which has become a "hot spot" in tumor differential diagnosis research in recent years [ 34 ]. The augmentation index level of the strong positive VM group was higher, and the in-depth analysis may be due to the fact that the contrast medium could enter with the plasma and diffuse through the tumor space, so that the contrast medium in the gap increased, thereby enhancing the tumor strengthening.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, unusual findings on ADC can serve as an early predictor of biological abnormality ( 12 ). After literatures review, the association between ADC values and clinical outcomes in PCNSL are only reported in rare studies with small samples, and the results are inconsistent between the existing studies ( 14 18 ). Also, no definite pretreatment ADC threshold values have yet been reported for prediction of R/R PCNSL.…”
Section: Introductionmentioning
confidence: 99%